Common variable immunodeficiency and autoimmune diseases: A 10-year single-center experience - Filiz Sadi Aykan; Fatih Çölkesen; Recep Evcen; Mehmet Kılınç; Eray Yıldız; Şevket Arslan (Archives of Rheumatology, 2024)
Objectives: This study aimed to determine the frequency of autoimmune diseases (ADs) accompanying common variable immunodeficiency (CVID) and evaluate clinical and immunological features, organ manifestation, and effects on malignancy and mortality. Patients and methods: The retrospective study was conducted with 85 patients (47 males, 38 females; median age: 38 years; range, 30 to 53 years) with CVID between January 2013 and January 2023. The patients were divided into two groups according to the presence of ADs: CVID patients with ADs [AD-CVID (+) group; n=36] and CVID patients without ADs [AD-CVID (–) group; n=49]. The clinical and immunological features of the groups were compared, and the effects on organ manifestations, malignancy development, and mortality were evaluated. Results: The diagnostic delay in the AD-CVID (+) group was 84 months and was longer than that in the AD-CVID (–) group. The most common AD was cytopenia, particularly immune thrombocytopenic purpura. Splenomegaly was the most common organ manifestation. Sjögren syndrome was the most common rheumatic disease. There was no difference between the immunoglobulin levels and lymphocyte subgroup levels, whereas the class-switched memory B cell levels were lower in the AD-CVID (+) group. While malignancy, particularly non-Hodgkin lymphoma, was more common in the AD-CVID (+) group, no difference was observed in mortality between the groups. Conclusion: Adult CVID patients with ADs have a longer diagnostic delay. Autoimmune conditions, particularly autoimmune cytopenias and inflammatory diseases, are much more common in patients with CVID than in the general population. Therefore, physicians’ awareness of autoimmune manifestations in CVID patients should be increased to prevent delays in diagnosis.